RITUAL TANAMAN ANDONG DAN KENTONGAN SEBAGAI PENGUSIR PEGEBLUK DALAM TRADISI ISLAM JAWA - Ilham Khafizhotul Mukaromah; Fardan Mahmudatul Imamah (Jurnal Ilmiah Ilmu Ushuluddin, 2021)
This article examines the plague expulsion ritual that uses the Tanaman Andong and kentongan as a spiritual effort in dealing with the Covid-19 pandemic in Sumberejo Village, Kandat District, Kediri Regency. A series of rituals had been conducted for two years during the pandemic are believed as “laku batin’ to prevent the plague attack in the village. This research uses Clifford Geertz's thick description approach which will provide a complete picture of the ritual process, materials, meanings of symbols, and people's beliefs about the Tanaman Andong and Kentongan rituals. Researchers used descriptive ethnographic methods, observations and in-depth interviews toward ritual practicers. As a result, the ritual of Tanaman Andong and Kentongan is a kind of ijtihad by a villager who is then trusted by his closest family, followed by 15 heads of families. There are several rituals of the Tanaman Andong and kentongan, they are larung offerings, selametan suro, installation of tolak bala’ of turmeric and rajah, and the installation of cinde in houses. Tanaman Andong means "dong" which in Javanese is called "ngaweruhi", understanding all the guidance given by Allah. Kentongan is a symbol of vigilance, so that with all the ritual efforts, the people feel of confidence and of security when living during a pandemic